Exploring the influence of different velocity fields on Wolf-Rayet star spectra - Lefever, Roel; Sander, Andreas A. C.; Shenar, T; Poniatowski, L G; Dsilva, K; Todt, H (Monthly notices of the Royal Astronomical Society, 2023)
Given their strong stellar winds, Wolf-Rayet (WR) stars exhibit emission line spectra that are predominantly formed in expanding atmospheric layers. The description of the wind velocity field $υ (r)$ is therefore a crucial ingredient in the spectral analysis of WR stars, possibly influencing the determination of stellar parameters. In view of this, we perform a systematic study by simulating a sequence of WR-star spectra for different temperatures and mass-loss rates using β-type laws with 0.5 ≤ β ≤ 20. We quantify the impact of varying $υ (r)$ by analysing diagnostic lines and spectral classifications of emergent model spectra computed with the Potsdam Wolf-Rayet (PoWR) code. We additionally cross-check these models with hydrodynamically consistent - hydro - model atmospheres. Our analysis confirms that the choice of the β exponent has a strong impact on WR-star spectra, affecting line widths, line strengths, and line profiles. In some parameter regimes, the entire range of WR subtypes could be covered. Comparison with observed WR stars and hydro models revealed that values of β ≳ 8 are unlikely to be realized in nature, but a range of β values needs to be considered in spectral analysis. UV spectroscopy is crucial here to avoid an underestimation of the terminal velocity $υ _∞$. Neither single- nor double-β descriptions yield an acceptable approximation of the inner wind when compared to hydro models. Instead, we find temperature shifts to lower T2/3 when employing a hydro model. Additionally, there are further hints that round-lined profiles seen in several early WN stars are an effect from non-β velocity laws.
Gesehen am 05.07.2023